The anthelmintic efficacy of natural plant cysteine proteinases against the rat tapeworm Hymenolepis diminuta in vivo - Mansur, F; Luoga, W; Buttle, DJ; Duce, IR; Lowe, A; Behnke, JM (Cambridge Univ Press, 2024)
Hymenolepis diminuta is a natural parasite of the common brown rat Rattus norvegicus, and provides a convenient model system for the assessment of the anthelmintic activity of novel drugs against cestodes. The experiments described in this paper indicate that treatment of rats infected with H. diminuta with a supernatant extract of papaya latex, containing a mixture of four cysteine proteinases, was moderately efficacious, resulting in a significant, but relatively small, reduction in worm burden and biomass. However, faecal egg output was not affected by treatment. In our experiments these effects were only partially dose-dependent, although specific inhibition by E-64 confirmed the role of cysteine proteinases as the active principles in papaya latex affecting worm growth but not statistically reducing worm burden. Data collected for a further 7 days after treatment indicated that the effects of papaya latex supernatant on worm loss and on worm growth were not enhanced. Our findings provide a starting point for further refinement in formulation and delivery, or assessment of alternative natural plant-derived cysteine proteinases in efforts to develop these naturally occurring enzymes into broad-spectrum anthelmintics, with efficacy against cestodes as well as nematodes.